Das cholinerge System in der Harnblase und der Neuroblastom-Zelllinie NS20Y der Maus : Acetylcholin-Freisetzung und nikotinische Acetylcholinrezeptoren - Wunsch, Julia Irene; Justus Liebig University Giessen (My University, 2009)
Acetylcholin (ACh) ist in der Harnblase nicht nur der wichtigste, für die Miktion verantwortliche Neurotransmitter, sondern auch ein lokales Signalmolekül, das im Urothel der Harnblase, einem non-neuronalen Gewebe, nachgewiesen wurde. Vom Urothel freigesetztes ACh könnte ebenso wie intravesikal instillierte Anticholinergika an cholinerge Rezeptoren binden. Folglich ist es von großem Interesse, ob ACh aus dem Urothel freigesetzt werden und über autokrine/parakrine Mechanismen auf cholinerge Rezeptoren wirken kann. Bisher liegen keine Ergebnisse darüber vor, welche Komponenten des cholinergen Systems ACh im Urothel freisetzen.

Acetylcholine (ACh) is not only the most important neurotransmitter of the urinary bladder responsible for miction but also a local signalling molecule found in the urothelium of the bladder, which is a non-neuronal tissue. ACh released by the urothelium may bind to cholinergic receptors, similary to intravesically instilled anticholinergica. Consequently, it is of great interest whether ACh can be synthesized and released by the urothelium itself and can act upon cholinergic receptors via autocrine/paracrine mechanisms. To date, there are no data which components of the cholinergic system release ACh in the urothelium. Muscarinic receptors have been investigated whereas it is unknown whether nicotinic receptors (nAChR) are also present in murine urothelium.
Keywords: ddc:610